2001
DOI: 10.1002/ijc.1357
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of homeobox geneHOXD3 induces coordinate expression of metastasis-related genes in human lung cancer cells

Abstract: Homeobox-containing genes are expressed in spatiotemporal fashion during embryogenesis and act as master transcription-regulating factors which control the expression of a variety of genes involved in morphogenesis. They are also expressed in a tissue-specific manner in normal adult tissues and appear to give cells spatial information in the maintenance of their architectural integrity. We transfected a HOXD3 class I homeobox-containing gene into human lung cancer A549 cells and investigated alterations in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 46 publications
(54 reference statements)
5
64
1
2
Order By: Relevance
“…12 Our previous studies showed that human lung cancer A549 cells transfected with HOXD3 gene acquired more metastatic, invasive and motile phenotypes. 13,14 We also observed that the transduction of HOXD3-antisense expression vectors into human melanoma cells dramatically diminished their invasive and motile activities. 15 Taken together, inappropriate expression of a particular HOX gene(s) is likely involved in tumor development and malignant progression such as invasion and metastasis and that the HOX gene(s) responsible for oncogenesis and/or tumor progression differs according to the organs or tissues from which the tumor cells have derived.…”
mentioning
confidence: 76%
“…12 Our previous studies showed that human lung cancer A549 cells transfected with HOXD3 gene acquired more metastatic, invasive and motile phenotypes. 13,14 We also observed that the transduction of HOXD3-antisense expression vectors into human melanoma cells dramatically diminished their invasive and motile activities. 15 Taken together, inappropriate expression of a particular HOX gene(s) is likely involved in tumor development and malignant progression such as invasion and metastasis and that the HOX gene(s) responsible for oncogenesis and/or tumor progression differs according to the organs or tissues from which the tumor cells have derived.…”
mentioning
confidence: 76%
“…Inversely, HoxD3 increases cell mobility and wound repair, while HoxB13 and Goosecoid promote invasion (Hansen et al, 2003;Zhao et al, 2005;Hartwell et al, 2006;Ohta et al, 2006). The cell spreading effect of HoxD3 correlates with its role in regulating cell-cell and cell-matrix interactions via the stimulation of integrin-a V b3 and reduction of Ecadherin (Hamada et al, 2001;Ohta et al, 2006). Cdx2 plays a key role in intestinal differentiation by upregulating intestinal-specific genes and inhibiting cell proliferation, which may contribute to antagonize cancer cell dissemination.…”
Section: Cdx2 Antagonizes Colon Cancer Cells Disseminationmentioning
confidence: 99%
“…Matrigel invasion assay was performed using a 24-well invasion chamber system (BD Biosciences, Bedford, MA) with Matrigel membrane (8.0-µm pore), as described in our previous report [15]. Briefly, each 750 µl of Ham's F12 medium supplemented with 20% FBS and 10 µg/ml of bovine fibronectin (chemoattractant) was placed in the lower compartment of the chamber.…”
Section: In Vitro Matrigel Invasion Assaymentioning
confidence: 99%